Flaky carbonyl iron powder wave-absorbing agent with porous double-shell structure and preparation method of flaky carbonyl iron powder wave-absorbing agent

By constructing a porous double-shell structure on the surface of sheet-like carbonyl iron powder, the problems of single loss mechanism and narrow bandwidth of carbonyl iron powder as a microwave absorber are solved, and a wide-band strong absorption effect is achieved.

CN121317894APending Publication Date: 2026-01-13SHANGHAI AEROSPACE EQUIPMENTS MANUFACTURER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511497829.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing carbonyl iron powder microwave absorbers suffer from a single loss mechanism and a narrow absorption bandwidth, making it difficult to achieve broadband and strong absorption.

Method used

Flake carbonyl iron powder was prepared by mechanical ball milling. A porous double-shell structure was formed by constructing a polydopamine/porogen inner shell and a metal oxide/porogen outer shell on its surface. An electromagnetic synergistic loss structure was formed by heat treatment.

Benefits of technology

It improves impedance matching characteristics and microwave absorption characteristics, enhances absorption performance, and achieves strong absorption effect over a wide frequency band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121317894A_ABST
    Figure CN121317894A_ABST
Patent Text Reader

Abstract

The invention discloses a flaky carbonyl iron powder wave-absorbing agent with a porous double-shell structure and a preparation method of the flaky carbonyl iron powder wave-absorbing agent. The method comprises the following steps: preparing flaky carbonyl iron powder (FCIP) by adopting a mechanical ball milling method, and then constructing a porous shell structure on the surface of the FCIP, the shell structure comprises two layers, the first layer is a porous carbon material, and the second layer is a porous oxide. According to the preparation method of the carbonyl iron powder core-shell structure with the porous shell layer, through the design of the porous shell layer structure, the impedance matching performance is enhanced, meanwhile, the wave absorbing capacity of the carbonyl iron powder is improved through shell layer components, and the carbonyl iron powder core-shell structure has important application prospects in the field of electromagnetic absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a porous double-shell structured sheet-like carbonyl iron powder microwave absorber and its preparation method, belonging to the field of stealth material preparation. Background Technology As the detection, tracking, and attack capabilities of defense systems worldwide become increasingly sophisticated, the battlefield is now exhibiting a trend towards greater depth and multidimensionality. Failure to effectively conceal oneself could result in being the first to suffer losses. To enhance the battlefield survivability of weapons and equipment such as fighter jets, drones, and submarines, countries around the world have successively developed radar stealth coatings based on carbonyl iron powder absorbing agents, which are widely used in the field of defense equipment.

[0002] However, traditional spherical carbonyl iron powder suffers from drawbacks such as a single loss mechanism and a narrow absorption bandwidth, which limit the effectiveness of carbonyl iron powder microwave absorbers. Current research primarily employs methods such as microstructure control, blending, and core-shell structures to compensate for some of the performance defects of carbonyl iron powder. Liu et al. effectively improved the microwave absorption performance of coatings by combining carbon black and carbonyl iron powder, achieving an absorption bandwidth of up to 10.1 GHz with a reflection loss value of less than -4 dB under a 2 mm thick coating condition (Applied Surface Science, 2010, 257, 842). Yang et al. prepared a carbonyl iron powder@silica microwave absorber, which improved the impedance matching characteristics of the coating but resulted in a loss of some microwave absorption characteristics (J. Phys. Chem. Solids, 2014, 75, 230-235). In summary, the preparation of broadband, high-absorption carbonyl iron powder microwave absorbers remains a challenge. Summary of the Invention

[0003] To address the shortcomings of existing technologies, this invention provides a porous double-shell structured sheet-like carbonyl iron powder microwave absorber and its preparation method. In this invention, sheet-like carbonyl iron powder (FCIP) is first prepared using mechanical ball milling. Then, polydopamine / porogen and metal oxide / porogen shells are sequentially constructed using different synthesis methods, followed by heat treatment to obtain the corresponding porous shells.

[0004] The objective of this invention is achieved through the following technical solution: This invention provides a method for preparing a porous double-shell structured sheet-like carbonyl iron powder microwave absorber. The microwave absorber uses sheet-like carbonyl iron powder (FCIP) as its core and two porous material layers as its shells. The inner shell is a polydopamine / porogen shell, and the outer shell is a metal oxide / porogen shell. The preparation method includes the following steps: S1. Flake carbonyl iron powder FCIP was prepared by mechanical ball milling; S2. Dissolve flake carbonyl iron powder FCIP in a mixed solution of dopamine / porogen. Under alkaline conditions, polydopamine and porogen co-assemble on the surface of FCIP to obtain the inner shell. S3. Dissolve the sheet-like carbonyl iron powder FCIP with an inner shell layer assembled on its surface in a mixed solution of titanium dioxide precursor / porogen. Under alkaline conditions, the titanium dioxide precursor and porogen are co-assembled on the surface of the inner shell layer. S4. After heat treatment, the porous double-shell structured sheet-like carbonyl iron powder microwave absorber is obtained.

[0005] In one embodiment of the present invention, in step S1, the ball milling time is 6 to 24 hours and the ball milling temperature is 20 to 30°C.

[0006] In one embodiment of the present invention, in step S1, the ball milling atmosphere is nitrogen or argon, and the ball milling medium is at least one of water and glycerol.

[0007] As one embodiment of the present invention, the aspect ratio of the sheet-like carbonyl iron powder FCIP obtained in step S1 is 5 to 10:1.

[0008] In one embodiment of the present invention, in step S2, the pore-forming agent is a copolymer of ethylene glycol and propylene glycol, including at least one of P123 and F127. The blending of P123 and F127 can adjust the pore size.

[0009] In one embodiment of the present invention, in step S2, the alkaline condition is achieved by adjusting the mixed solution to alkaline using ammonia.

[0010] As one embodiment of the present invention, in step S2, the co-assembly reaction temperature is 60-80 ℃ (theoretically, polymerization can be carried out at room temperature, but a slightly higher temperature is required to achieve co-assembly; in this invention, it is controlled at 60-80 ℃), and the co-assembly time is 6-30 h; In one embodiment of the present invention, in step S2, the ratio of FCIP to the mixed solution of dopamine / porogen is 1-3g:100ml.

[0011] In one embodiment of the present invention, in step S2, the concentration of dopamine in the dopamine / porogen mixed solution is 1-3 mg / mL, and the concentration of porogen is 8-12 mg / mL.

[0012] In one embodiment of the present invention, in step S3, the alkaline condition is to adjust the solution to alkalinity (e.g., pH ≥ 8) using ammonia.

[0013] In one embodiment of the present invention, in step S3, the pore-forming agent is a copolymer of ethylene glycol and propylene glycol, including at least one of P123 and F127.

[0014] In one embodiment of the present invention, in step S3, the co-assembly reaction temperature is 120–180 °C and the co-assembly time is 6–12 h.

[0015] As one embodiment of the present invention, in step S3, the ratio of the amount of the mixed solution of the sheet carbonyl iron powder FCIP with the inner shell layer assembled on the surface to the titanium dioxide precursor / porogen is 1 ± 0.1 g: 15 ml.

[0016] In one embodiment of the present invention, in step S3, the concentration of the titanium dioxide precursor in the mixed solution of titanium dioxide precursor / porogen is 0.08-0.12 mol / L, and the concentration of the porogen is 50-100 mg / ml.

[0017] In one embodiment of the present invention, in step S4, the heat treatment temperature is 600~900 ℃ and the time is 1~3h.

[0018] As one embodiment of the present invention, the thickness of the double shell of the porous double-shell structured sheet-like carbonyl iron powder microwave absorber obtained by heat treatment is 50-200 nm, and the average pore size of the pores in the shell is 20-45 nm.

[0019] As one embodiment of the present invention, the thickness of the inner shell layer in the double shell layer is 20~80 nm; the thickness of the outer shell layer is 30~120 nm.

[0020] The porous shell-structured sheet-like carbonyl iron powder radar absorber prepared by the aforementioned method, and its use in the preparation of radar stealth coatings or stealth equipment products, are both within the scope of protection of this invention. The porous shell-structured sheet-like carbonyl iron powder radar absorber of this invention has significant application prospects in stealth equipment such as drones and fighter jets.

[0021] This invention constructs a porous shell structure by first assembling a polydopamine / porogen inner shell and a metal oxide / porogen outer shell on the surface of sheet-like carbonyl iron powder FCIP, followed by heat treatment. For polydopamine, heat treatment serves the purposes of carbonization and pore formation; while for the titanium dioxide porous structure, heat treatment both facilitates the formation of the TiO2 crystal structure and creates pores (high temperature can remove the porogen), thereby obtaining a structure with electromagnetic synergistic loss, which is then coupled with porous shell scattering to enhance microwave absorption performance.

[0022] Compared with the prior art, the present invention has the following beneficial effects: Compared with previous methods for improving the microwave absorption performance of carbonyl iron powder, this invention provides a method for preparing a porous double-shell structured sheet-like carbonyl iron powder microwave absorber. By designing a core-shell structure of carbonyl iron powder with a porous double shell, the impedance matching characteristics are improved on the one hand, and the porous double shell enhances the microwave absorption characteristics on the other hand. Attached Figure Description

[0023] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 Electron micrograph of sheet-like carbonyl iron powder; Figure 2 This is an electron microscope image of porous shell carbonyl iron powder. Detailed Implementation

[0024] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0025] To further illustrate the technical effects of the present invention, relevant experiments were conducted.

[0026] Example 1 This embodiment relates to a method for preparing a porous carbon shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL), and 1 g of F127 is added. After complete dissolution, the pH of the solution is adjusted with ammonia (pH is 8.5). The polymerization reaction is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After heat treatment (700 ℃) for 2 h, a porous carbon shell sheet-like carbonyl iron powder microwave absorber is obtained. The porous carbon shell thickness is 55 nm, and the pore size is 20 nm.

[0027] Example 2 This embodiment relates to a method for preparing a porous carbon shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL), and 1 g of F127 and P123 (mass ratio 1:1) are added. After complete dissolution, the pH of the solution is adjusted with ammonia (pH 8.5). The polymerization reaction is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After heat treatment (700 ℃) for 2 h, a porous carbon shell sheet-like carbonyl iron powder microwave absorber is obtained. The porous carbon shell thickness is 58 nm, and the pore size is 30 nm.

[0028] Example 3 This embodiment relates to a method for preparing a porous carbon shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL), and 1 g of P123 is added. After complete dissolution, the pH of the solution is adjusted with ammonia (pH is 8.5). The polymerization reaction is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After heat treatment (700 ℃) for 2 h, a porous carbon shell sheet-like carbonyl iron powder microwave absorber is obtained. The porous carbon shell thickness is 65 nm, and the pore size is 35 nm.

[0029] Example 4 This embodiment relates to a method for preparing a porous oxide shell-shelled sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 1 g of FCIP is dissolved in 15 mL of 0.1 mol / L tetrabutyl titanate solution, and 1 g of F127 is added. After complete dissolution, the solution is adjusted to alkalinity (pH≥8) with KOH. The product is obtained by a solvothermal method at a reaction temperature of 150 ℃ for 8 h. After subsequent heat treatment (700 ℃, 2 h), a porous double-shell sheet-like carbonyl iron powder microwave absorber is obtained. The porous oxide shell thickness is 120 nm, and the pore size is 41 nm.

[0030] Example 5 This embodiment relates to a method for preparing a porous carbon / porous oxide double-shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: Spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8 (morphology as shown in the figure). Figure 1 Then, 2 g of FCIP was dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL), and 1 g of F127 and P123 (mass ratio 1:1) were added. After complete dissolution, the pH of the solution was adjusted with ammonia (pH 8.5). The polymerization reaction was carried out at 70 °C for 24 h under stirring at 30 rpm. After centrifugation, flake carbonyl iron powder with polydopamine / porogen shell was obtained. Then, 1 g of flake carbonyl iron powder with polydopamine / porogen shell was dissolved in 15 mL of 0.1 mol / L tetrabutyl titanate solution, and 1 g of F127 was added. After complete dissolution, the solution was adjusted to alkalinity (pH ≥ 8) with KOH. The product was obtained by solvothermal method at 150 °C for 8 h. After subsequent heat treatment (700 °C, 2 h), a porous double-shell flake carbonyl iron powder microwave absorber was prepared. See Figure 2 The inner shell has a thickness of 60 nm; the outer shell has a thickness of 110 nm and a pore size of 38 nm.

[0031] Example 6 This embodiment relates to a method for preparing a porous carbon / porous oxide double-shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: Spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL), and 1 g of F127 and P123 (mass ratio 1:1) are added. After complete dissolution, the pH of the solution is adjusted to 8.5 with ammonia. The polymerization reaction is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After centrifugation, sheet-like carbonyl iron powder with a polydopamine / porogen shell is obtained. Then, 1 g of the polydopamine / porogen shell sheet-like carbonyl iron powder is dissolved in 15 mL of 0.1... In a mol / L tetrabutyl titanate solution, 1 g of P123 was added. After complete dissolution, the solution was adjusted to alkalinity (pH≥8) with KOH. The product was obtained by a solvothermal method at a reaction temperature of 150℃ for 12 h. After subsequent heat treatment (700℃, 2 h), a porous double-shell plate-like carbonyl iron powder microwave absorber was prepared. The inner shell thickness was 65 nm, the outer shell thickness was 105 nm, and the pore size was 45 nm.

[0032] Comparative Example 1 This comparative example relates to a method for preparing a flake-shaped carbonyl iron powder microwave absorber. The specific preparation includes the following steps: ball milling spherical carbonyl iron powder (SCIP) into flake-shaped carbonyl iron powder (FCIP) using a ball milling method, wherein the ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, the ball milling medium is water, and the obtained FCIP has an aspect ratio of 8.

[0033] Comparative Example 2 This comparative example relates to a method for preparing a flake-shaped carbonyl iron powder microwave absorber. The specific preparation includes the following steps: Spherical carbonyl iron powder (SCIP) is ball-milled into flake-shaped carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of a fresh dopamine ethanol-water mixture (2 mg / mL), and 1 g of PS is added. 100 -b-PEO 114 After the micelles were completely dissolved, the pH of the solution was adjusted to 8.5 with ammonia. The polymerization reaction was carried out at 70 °C for 24 h under stirring at 30 rpm. The resulting product was then centrifuged to obtain PS. 100 -b-PEO 114 / The porogen shell consists of flake-shaped carbonyl iron powder; then 1 g is dissolved in 15 mL of 0.1 mol / L tetrabutyl titanate in an ethanol-water mixture, and 1 g of PS is added. 100 -b-PEO 114 Micelles were completely dissolved, and the solution was adjusted to alkalinity (pH≥8) with KOH. The product was obtained by solvothermal method at 150℃ for 8 hours. After subsequent heat treatment (700℃, 2 hours), a porous double-shell plate-like carbonyl iron powder microwave absorber was prepared. The porous oxide shell thickness was 130 nm and the pore size was 42 nm.

[0034] Comparative Example 3 This comparative example relates to a method for preparing a flake-shaped carbonyl iron powder microwave absorber. The specific preparation includes the following steps: Spherical carbonyl iron powder (SCIP) is ball-milled into flake-shaped carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of a fresh pyrrole ethanol-water mixed solution (2 mg / mL), and 1 g of F127 and P123 (mass ratio 1:1) is added. After complete dissolution, 1 g of FeCl3 is added to initiate polymerization. The polymerization reaction is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After centrifugation, flake-shaped carbonyl iron powder with a polypyrrole / porogen shell is obtained. Then, 1 g of the FCIP is dissolved in 15 mL of a 0.1 mol / L tetrabutyl titanate ethanol-water mixed solution, and 1 g of FeCl3 is added... F127 was completely dissolved, and the solution was adjusted to alkalinity (pH≥8) with KOH. The product was obtained by solvothermal method at 150℃ for 8 hours. After subsequent heat treatment (700℃, 2 hours), a porous double-shell plate-like carbonyl iron powder microwave absorber was prepared. The thickness of the porous oxide shell was 135 nm and the pore size was 52 nm.

[0035] Comparative Example 4 This comparative example relates to a method for preparing a carbon / oxide double-shell sheet-like carbonyl iron powder microwave absorber. The specific preparation includes the following steps: Spherical carbonyl iron powder (SCIP) is ball-milled into sheet-like carbonyl iron powder (FCIP) using a ball milling method. The ball milling time is 12 h, the ball milling temperature is 25 ℃, the ball milling atmosphere is nitrogen, and the ball milling medium is water. The resulting FCIP has an aspect ratio of 8. Then, 2 g of FCIP is dissolved in 100 mL of fresh dopamine aqueous solution (2 mg / mL). The pH of the solution is adjusted to 8.5 with ammonia. Polymerization is carried out at 70 ℃ for 24 h under stirring at 30 rpm. After centrifugation, sheet-like carbonyl iron powder with a polydopamine shell is obtained. Then, 1 g is dissolved in 15 mL of 0.1... In a mol / L tetrabutyl titanate solution, the solution was adjusted to alkalinity (pH≥8) with KOH, and the product was obtained by solvothermal method at a reaction temperature of 150℃ for 8 h. After subsequent heat treatment (700℃, 2 h), a double-shell plate-like carbonyl iron powder microwave absorber was obtained, with an inner shell thickness of 55 nm and an oxide shell thickness of 135 nm.

[0036] The microwave absorption performance tests of the above-described embodiments and comparative materials are shown in Table 1: Table 1. Microwave absorption performance test results

[0037] Note: The microwave absorption performance of samples from 2 to 18 GHz was evaluated using the coaxial method. The samples were mixed with polyethylene wax and then molded into concentric ring-shaped samples for testing. The sample content was 50 wt%, the size was 2 cm, and the molding temperature was 40 degrees Celsius.

[0038] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a porous double-shell structure sheet-shaped carbonyl iron powder wave-absorber, characterized in that, The wave-absorbing agent takes flaky carbonyl iron powder FCIP as the core, and takes two layers of porous materials as the shell, with the inner shell layer being a polydopamine / pore-forming agent shell layer and the outer shell layer being a metal oxide / pore-forming agent shell layer; the preparation method comprises the following steps: S1, preparing flaky carbonyl iron powder FCIP by mechanical ball milling; S2, dissolving the flaky carbonyl iron powder FCIP in a mixed solution of dopamine / pore-forming agent, and co-assembling polydopamine and the pore-forming agent on the surface of the FCIP under alkaline conditions to obtain the inner shell layer; S3, dissolving the flaky carbonyl iron powder FCIP with the surface assembled with the inner shell layer in a mixed solution of titanium dioxide precursor / pore-forming agent, and co-assembling the titanium dioxide precursor and the pore-forming agent on the surface of the inner shell layer under alkaline conditions; S4, obtaining the porous double-shell structure flaky carbonyl iron powder wave-absorbing agent after heat treatment.

2. The production method according to claim 1, characterized by, In step S1, the ball milling time is 6-24 h, the ball milling temperature is 20-30 DEG C, the ball milling atmosphere is nitrogen or argon, and the ball milling medium is at least one of water and glycerol.

3. The preparation method according to claim 1, characterized in that, The aspect ratio of the flaky carbonyl iron powder FCIP prepared in step S1 is 5-10:

1.

4. The method of claim 1, wherein, The pore-forming agent is a copolymer of ethylene glycol and propylene glycol, and includes at least one of P123 and F127.

5. The preparation method according to claim 1, characterized in that, In step S2, the dosage ratio of the FCIP to the mixed solution of dopamine / pore-forming agent is 1-3 g:100 ml; and / or, in the mixed solution of dopamine / pore-forming agent, the dopamine concentration is 1-3 mg / mL, and the pore-forming agent concentration is 8-12 mg / mL; and / or, the co-assembly reaction temperature is 60-80 DEG C, and the co-assembly time is 6-30 h.

6. The method of claim 1, wherein, In step S3, the co-assembly reaction temperature is 120-180 DEG C, and the co-assembly time is 6-12 h; and / or, the dosage ratio of the flaky carbonyl iron powder FCIP with the surface assembled with the inner shell layer to the mixed solution of titanium dioxide precursor / pore-forming agent is 1±0.1 g:15 ml; and / or, in the mixed solution of titanium dioxide precursor / pore-forming agent, the titanium dioxide precursor concentration is 0.08-0.12 mol / L, and the pore-forming agent concentration is 50-100 mg / ml.

7. The preparation method according to claim 1, characterized in that, In step S4, the heat treatment temperature is 600-900 DEG C, and the time is 1-3 h.

8. The method of claim 1, wherein, The thickness of the double shell layer of the porous double-shell structure flaky carbonyl iron powder wave-absorbing agent obtained after heat treatment is 50-200 nm, and the average pore size of the porous shell layer is 20-45 nm.

9. The production method according to claim 8, characterized by, The thickness of the inner shell layer in the double shell layer is 20-80 nm, and the thickness of the outer shell layer is 30-120 nm.

10. Use of the porous shell structure flaky carbonyl iron powder wave-absorbing agent prepared by the method of any one of claims 1-9 in preparing radar stealth coating or preparing stealth equipment products.

Citation Information

Patent Citations

  • Low-frequency wave-absorbing material and preparation method thereof

    CN111285671A

  • High-temperature-resistant dual-core-shell type electric-magnetic loss synergistic flaky carbonyl iron powder wave-absorbing agent and preparation method thereof

    CN117509744A